THE GENUS MASTIXIA BL. (CORNACEAE) IN CEYLON - a. j. g. h. KOSTERMANS (Research Center for Biology, 1982)
Five species of Mastixia are found in Sri Lanka, of which M. congylos and M. nimalii are here described for the first time, whereas M. tetrandra var. thwaitesii is raised to specific rank as M. montana. M. arborea does not occur in Sri Lanka. A key to the species is presented and the specimens examined are enumerated.